Adaptations for Wear Resistance and Damage Resilience: Micromechanics of Spider Cuticular "Tools". (25th June 2020) - Tadayon, Maryam; Younes‐Metzler, Osnat; Shelef, Yaniv; Zaslansky, Paul; Rechels, Alon; Berner, Alex; Zolotoyabko, Emil; Barth, Friedrich G.; Fratzl, Peter; Bar‐On, Benny; Politi, Yael
Abstract: In the absence of minerals as stiffening agents, insects and spiders often use metal‐ion cross‐linking of protein matrices in their fully organic load‐bearing "tools." In this comparative study, the hierarchical fiber architecture, elemental distribution, and the micromechanical properties of the manganese‐ and calcium‐rich cuticle of the claws of the spider Cupiennius salei, and the Zn‐rich cuticle of the cheliceral fangs of the same animal are analyzed. By correlating experimental results to finite element analysis, functional microstructural and compositional adaptations are inferred leading to remarkable damage resilience and abrasion tolerance, respectively. The results further reveal that the incorporation of both zinc and manganese/calcium correlates well with increased biomaterial's stiffness and hardness. However, the abrasion‐resistance of the claw material cross‐linked by incorporation of Mn/Ca‐ions surpasses that of many other non‐mineralized biological counterparts and is comparable to that of the fang with more than triple Zn content. These biomaterial‐adaptation paradigms for enhanced wear‐resistance may serve as novel design principles for advanced, high‐performance, functional surfaces, and graded materials. Abstract : Many load‐bearing biological materials incorporate metal‐ion cross‐linking as reinforcement in otherwise fully organic matrices. In the spider, Cupiennius salei, the fangs, used for venom injection are rich with zinc ions, whereas the claws, used for locomotion, incorporate manganese and calcium ions. The biological distribution of these metal ions is found to be adapted to their mechanical role.